2022
DOI: 10.1111/agec.12727
|View full text |Cite
|
Sign up to set email alerts
|

Trade and food security in a climate change‐impacted world

Abstract: Today's climate‐turbulent world is rife with food insecurity—threatening economic development trajectories by stunting growth, subsequently reducing employability and labor productivity, especially for developing countries. The pandemic has exacerbated these adverse effects and reveals the critical need to put in place policies that can safeguard and sustain trade flows in agricultural products. For the vast majority of countries, food security cannot be guaranteed by domestic production alone. If certain crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
(32 reference statements)
2
6
0
Order By: Relevance
“…In other words, the results have proven that climate change is threating agricultural trade flows in the region such that the region may continue to be a net-food importer. The results corroborate those of Tekce and Deniz [15], Khan et al [17], Adesete et al [25], Fusco [27], Baptista et al [11], Affoh et al [24], Brenton et al [2] and Dumortier et al [1] who in their respective studies also found negative impacts of climate change on agricultural trade.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In other words, the results have proven that climate change is threating agricultural trade flows in the region such that the region may continue to be a net-food importer. The results corroborate those of Tekce and Deniz [15], Khan et al [17], Adesete et al [25], Fusco [27], Baptista et al [11], Affoh et al [24], Brenton et al [2] and Dumortier et al [1] who in their respective studies also found negative impacts of climate change on agricultural trade.…”
Section: Resultssupporting
confidence: 87%
“…In this regard, climate change has become one of the most pressing issues affecting attainment of sustainable agriculture and food security [1]. One area where it is particularly concerning is in emerging economies, where agriculture plays a significant role in their economy and food security [2]. Climate change has led to unpredictable weather patterns, droughts, floods, and extreme temperatures that have affected crop yields and livestock production [3].…”
Section: Introductionmentioning
confidence: 99%
“…The general consensus in the literature is that trade will play an important role in adjusting to the shifts in agricultural and food production patterns resulting from climate change (Brenton et al, 2022;Nelson et al, 2009Nelson et al, , 2010, improving household food access by moderating price increases, and reducing shocks to food availability (Brown & Kshirsagar, 2015;Brown et al, 2017;Lybbert & Sumner, 2012). However, in order to ensure that the stabilizing power of trade is realized, investments in maintaining, expanding, and climate-proofing existing infrastructure are considered necessary, particularly in order to reach geographically isolated, poor, and/or socially marginalized communities (Thacker et al, 2019).…”
Section: Distribution Processing and Marketingmentioning
confidence: 99%
“…Given the limited country 2 Ajewole et al (2022) point out that the movement of labor and other factors of production out of agriculture is generally regarded as a key component of economic development. Further, Brenton et al (2022) note that exports of agricultural products provide a major source of income, especially in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%